Результати досліджень видобутку бурштину гідромеханічним способом - Маланчук, З.; Корнієнко, В.; Маланчук, Є. (Розробка родовищ, 2017)
Purpose. To specify parameters of the relationship between sandy rock and vibrohydraulic intensifier as well as to justify the use of hydromechanical method to intensify amber extraction. Findings. Parameters of the relationship between sandy rock and vibrohydraulic intensifier have been established by detecting the intensifier amplitude, frequency, rock density, water and air supply into the massif, which allows to create a continuous suspension medium and increase amber mining productivity. Originality. For the first time, the research has established the influence of vibration, water and air on the liquefaction of sandy media which is achieved by vibrohydraulic dredger in the natural environment, depending on the intensity of gas-liquid mixture feeding into the amber containing massif. It was established that water and air consumption is directly proportional to the volume of the working space, penetration rate; medium porosity, density and moisture content.